Carbon Dioxide Capture: An Effective Way to Combat Global Warming - Creamer, Anne Elise; Gao, Bin.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This topical brief summarizes the various options available for carbon capture and presents the current strategies involved in CO2 reduction. The authors focus on current CO2 capture technologies that facilitate the reduction of greenhouse gas (CO2) emissions and reduce global warming. This short study will interest environmental researchers, teachers and students who have an interest in global warming.
Overview of Greenhouse Gases and Global Warming -- Overview of CO2 Capture Technology -- Adsorbents for CO2 Capture -- Absorbents for CO2 Capture -- CO2 Reduction and Utilization.
Keywords: Chemistry; Fossil fuels; Climate change; Chemical engineering; Chemistry; Industrial Chemistry/Chemical Engineering; Climate Change/Climate Change Impacts; Fossil Fuels (incl. Carbon Capture).; Electronic books